The use of social media in teaching and learning for dance education at tertiary level / Muhammad Fairul Azreen Mohd Zahid & Ahmad Kamal Basyah Sallehuddin - Mohd Zahid, Muhammad Fairul Azreen; Basyah Sallehuddin, Ahmad Kamal (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Online learning emerges as the oft talked constraint among educators especially, at the Tertiary level. Most students are encountering hardships in accessing the internet without hiccups, especially during the movement control order/quarantine/self-isolation due to the ongoing pandemic caused by Covid-19. However, internet access for the use of social media is easily available and not limited. As a result, teaching and learning techniques focusing on students of higher learning institutions can be done using social media apps such as Facebook, TikTok, YouTube, and Instagram. The aforementioned social media apps served as a platform to raise interest and increase attraction in dealing with learning activities in 21st century.